A Location-Aware and Greedy Cross-Layer Routing Protocol for Flying Ad-hoc Networks - Moreira, Rian T. D.; Medeiros, Dianne S. V. (Journal of the Brazilian Computer Society, 2024)
The Flying Ad-hoc Networks (FANETs) enhance the coverage capacity in cellular networks by forwarding data in multiple hops using Unmanned Aerial Vehicles (UAVs). Nevertheless, unlike classic ad-hoc networks, FANETs have specific characteristics, such as free movement in three dimensions and very high-speed nodes. These characteristics lead to a more complex and dynamic mobility pattern compared to other ad-hoc networks, generating more frequent topology changes. This paper proposes the Greedy Weighted Perimeter Routing Protocol (GWPRP), which aims to improve networking performance. GWPRP is a location-aware and greedy cross-layer routing protocol based on a classic protocol for vehicular networks, the Greedy Perimeter Stateless Routing (GPSR). Following a similar greedy strategy, GWPRP forwards packets based only on local information obtained from neighbors, which considers link and network layer information, local link stability, and node location. We assess the protocol in a simulated environment, comparing its performance with GPSR and Energy Efficient Hello Ad-hoc On-Demand Distance Vector (EE HELLO AODV), a variant of AODV for FANETs. The results show that GWPRP achieves a higher packet delivery ratio with smaller control overhead and lower average end-to-end delay and jitter.